Policy Analysis on The Removal of Age Limits in Indonesian Labor Recruitment: A Public Policy Perspective - Rivany, Deaotna; Supriyatno, Budi; Hakim, Azis (Dinasti Publisher, 2026)
The removal of age limits in recruitment processes is a vital issue in achieving justice and equal opportunity for all citizens. Although the government has not yet issued a formal regulation explicitly abolishing age limits, several non-regulatory policy instruments, including the Circular Letter of the Minister of Manpower of the Republic of Indonesia Number M/06/HK.04/V/2025 concerning the Prohibition of Discrimination in the Labor Recruitment Process, indicate a policy shift toward more inclusive recruitment practices. This study aims to analyze the dynamics of the policy to abolish age limits from a public policy perspective, including agenda setting, policy instruments, and public readiness for its implementation. The research uses a qualitative descriptive approach with document analysis and public policy theory. The results show that the policy of abolishing age limits is currently at the